Assessment on density discrepancy of supercritical reactive hydrocarbon fuels using the Monte-Carlo method. (November 2019) - Yu, Xuanfei; Zhang, Silong; Bao, Wen; Zhou, Weixing; Yu, Daren
Abstract: In order to assist the developing of mass flow rate measurement methods for supercritical reactive hydrocarbon fuels, the possible variation of fuel density caused by thermal cracking is evaluated. A one-dimensional model of the flow process inside scramjet cooling channels is developed and validated through experiment for the assessment, with the Monte-Carlo method adopted to define the test conditions. The results indicate that pyrolysis of the fuel is very sensitive to the distribution of heat flux (HFD). For the case of total heating power of 12.5 kW, the relative discrepancies of 88% and 7.2% are observed for channel outlet fuel mass conversion and density respectively due to the variation of HFD, with the corresponding outlet temperature is varied between 890 and 950 K accordingly. Also it reveals that within the entire chemical non-equilibrium region, the maximum difference of fuel mass conversion can be as high as 60% for equal channel outlet fuel temperature, with the maximum relative discrepancy for fuel density is up to 140% approximately. Meanwhile, it seems that the density discrepancy cannot be decreased to the acceptable level by selecting the design and operation parameters of the cooling channel, i.e., within the interval of fuel pressure, mass flow flux and tube length evaluated, the maximum relative discrepancy of channel outlet fuel density varies between 112.1 and 150%, which is far beyond the proposed maximum acceptable value in term of mass flow measurement. Highlights: Monte-Carlo simulation is performed to bound the variation of cracked fuel density. The impact of heat flux distribution on final states of cracked fuel is remarkable. Large density discrepancy occurs in thermal cracking region at a given temperature. The impact pressure, channel length and flow flux is minor on density discrepancy.